Understanding the Nutritional Status of Agricultural Women in Village Rangil, Ganderbal District of Kashmir - Bilal Ahmad Bhat; Nusrat Aziz; Bisma Zargar; Shafia Jan (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2025)
Agricultural women is expected to perform both the duties of housewife and farming women. Thus, the nutrition status and dietary pattern of agricultural women can be affect due to heavy mental and physical efforts. The main objectives of the current study were to examine the nutritional status of Agricultural women. Current study includes 200 Agricultural women, selected randomly from Rangil village, Ganderbal district of Kashmir valley, J&K. A well designed and structured Questionnaire was employed to collect the data on General information and Dietary Recall. The data collected was analysed using appropriate statistical tool. Nutritive value was taken and calculated and compared with Recommended Dietary Allowances. The results of the study shows that out of 200 respondents on the basis of BMI, we observed that 46% respondents were normal, 33.5% were over weight, 9.5% were Obese I, 5.5% were under weight, 3.5% respondents were severely under weight and 2% respondents were Obese II. Statistically it was found that there was a significant difference among various BMI groups as (P< 0.01). The results revealed that in majority of cases nutrients studied are not meeting the Recommended Dietary Allowances. Further, statistically, there was a significant difference in BMI between married and unmarried respondents (P<0.01). It was concluded that to tackle the health problems of women living in Rangil village of district Ganderbal, Kashmir valley, we require a comprehensive approach